CHARACTERISTICS OF GOOD ENGLISH TEACHERS BASED ON THE PERCEPTION OF THE STUDENTS FROM DIFFERENT LEARNING STYLES AND PERSONALITIES - Fausiah Sriyuliyana (Universitas Muhammadiyah Sorong, 2016)
The research aims are (i) Identifying the characteristics of good English teachers in SMAN 3 Sinjai Selatan. (ii) Knowing the characteristics of good English teacher based on the students’ learning style. (iii) Knowing the characteristics of good English teacher based on the students’ personality. This research was done by using a qualitative approach. The data were collected by using two instruments i.e. questionnaires and in depth interview. The results of this study reveal that (i) The characteristics of good English teacher based on the students’ perception in SMAN 3 Sinjai Selatan are categorized into four different categories, namely proficiency, pedagogical (both conceptual and practical), socio-affective and psychological aspect. The last category was the additional category in which age included in and differently from the work of Gi and Hyo (2006) that only specified three categories, namely proficiency, pedagogical and socio-affective skills. (ii) In general, the characteristics of good English teacher based on the students’ learning style are dominantly in pedagogical aspect. Visual learners want English teacher who can keep the students’ focus and concentration in their learning; auditory learners expect English teacher who can engage the students’ motivation and interest toward learning English; and haptic learners propose the English teacher who concerns on the process rather than the achievement of the students in learning. (iii) The characteristics of good English teacher proposed by high school students based on their personality are dominantly on the teacher’s pedagogical and socio-affective aspects. Only a few ideas of the students that concern on the teacher’s proficiency and psychological aspect.